Demonstration of Polysaccharide Capsule in Campylobacter jejuni Using Electron Microscopy - Karlyshev, Andrey V. (American Society for Microbiology, 2001)
Recently, we reported that Campylobacter jejuni, an important gastrointestinal pathogen, has the genetic determinants to produce a capsular polysaccharide (Karlyshev et al., Mol. Microbiol. 35:529–541, 2000). Despite these data, the presence of a capsule in these bacteria has remained controversial. In this study we stain C. jejuni cells with the cationic dye Alcian blue and demonstrate for the first time by electron microscopy that C. jejuni cells produce a polysaccharide capsule that is retained in the coccoid form but is absent in a kpsM mutant.